PENGARUH PEMANFAATAN ABU PECAHAN TERUMBU KARANG DAN ABU SEKAM PADI SEBAGAI PENGGANTI SEMEN TERHADAP KUAT TEKAN BETON - Afrizal, Yuzuar; Ramahayati, Nuzhi; Islam, Mukhlis (Inersia: Jurnal Teknik Sipil, 2019)
Portland cement is a relatively expensive type of cement when used on constructions requiring simple requirements. Local material utilization using ash fragments of coral reefs and rice husk ash is one of the solutions. The objectives of this study is to determine the value of concrete compressive strength in each variation of cement replacement used were 2.5%, 5%, 7.5% and 10%, each variation consists of 70% ash fragment of coral reefs and 30% rice husk ash from the volume of cement used. The cube specimen with a size of (15x15x15) cm as many as 20 specimen were prepared. Concrete mixture according to SNI 03-2834-2000 used 0.5 cement water ratio and 60-100 mm of slump. The result of the compressive strength of concrete variation every percentage increase has increased and decreased from the result of the normal concrete compressive strength of 368.24 kg/cm2. Maximum increase occurred in the concrete compressive strength variation 7.5% of 384.76 kg/cm2 and decreased on the concrete compressive strength variation 10% of 367.40 kg/cm2.